A Literature Review Of Interventions For Early Childhood Aggressive Behaviour In Indonesia - Dewi, Komang Dea Teja Amanda; Susilawati, Luh Kadek Pande Ary (UIN Sultan Maulana Hasanudin Banten, 2024)
The emergence of aggressive behavior in a child can interfere with their developmental process. Aggressive behavior encompasses intentional physical, verbal, or a combination of actions aimed at causing harm to others, such as expressing anger without apparent cause, threatening, attacking, or informing an adult that another child is wrong. A variety of intervention methods can help reduce aggressive behavior in children. In order to identify effective strategies for addressing early childhood aggression and preventing the emergence of developmental barriers, this study employs the literature review method. The research has found three aggressive behavioral interventions in early childhood: storytelling, reinforcement, and role-play.